Consanguineous familial study revealed biallelic FIGLA mutation associated with premature ovarian insufficiency - Beili Chen; Lin Li; Jing Wang; Tengyan Li; Hong Pan; Beihong Liu; Yiran Zhou; Yunxia Cao; Binbin Wang (BMC, 2018)
Abstract Background To dissect the genetic alteration in two sisters with premature ovarian insufficiency (POI) from a consanguineous family. Methods Whole-exome sequencing technology was used in the POI proband, bioinformatics analysis was carried out to identify the potential genetic cause in this pedigree. Sanger sequencing analyses were performed to validate the segregation of the variant within the pedigree. In silico analysis was also used to predict the effect and pathogenicity of the variant. Results Whole-exome sequencing analysis identified novel and rare homozygous mutation associated with POI, namely mutation in FIGLA (c.2 T > C, start codon shift). This homozygous mutation was also harbored by the proband's sister with POI and was segregated within the consanguineous pedigree. The mutation in the start codon of the FIGLA gene alters the open reading frame, leading to a FIGLA knock-out like phenotype. Conclusions Biallelic mutations in FIGLA may be the cause of POI. This study will aid researchers and clinicians in genetic counseling of POI and provides new insights into understanding the mode of genetic inheritance of FIGLA mutations in POI pathology.